2020
DOI: 10.18805/ijar.b-3969
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Substitution of Palm Oil by Rapeseed Oil at Different Levels on Growth Performance and Economics of Broilers

Abstract: Background: Fat and oil are commonly used in poultry diets to increase energy density and also to increase the palatability of feed, feed efficiency and for deposition of fat in broilers. Thus a study was proposed to find the effects of dietary replacement of saturated fatty acid rich palm oil (PO) by omega-3 rich rapeseed oil (RO) on growth performance and economics in broilers. Method: The growth performance feeding trial was conducted in 160 day-old broilers (vencobb 400) with four treatment groups (G1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Conversely some studies stated that, dietary fatty acid profile influences better body weight gain in broilers fed with omega 3 rich oil sources like sunflower oil, canola oil and soya bean oil compared to saturated fat rich palm oil as presence of polyunsaturated fatty acids has better intestinal absorption due to hydrolysis of monoglyceride and micelle formation compared to saturated fatty acids (Poorghasemi et al, 2018). Similarly feeding of omega 3 rich rapeseed oil at 0.75 to 1.5% level was reported to improve the production performance in broilers (Sudharsan et al, 2020). In our study, the FCE in the birds of LOG diet was found best with highest ADG and total weight gain and lowest ADFI.…”
Section: Production Performancesupporting
confidence: 59%
“…Conversely some studies stated that, dietary fatty acid profile influences better body weight gain in broilers fed with omega 3 rich oil sources like sunflower oil, canola oil and soya bean oil compared to saturated fat rich palm oil as presence of polyunsaturated fatty acids has better intestinal absorption due to hydrolysis of monoglyceride and micelle formation compared to saturated fatty acids (Poorghasemi et al, 2018). Similarly feeding of omega 3 rich rapeseed oil at 0.75 to 1.5% level was reported to improve the production performance in broilers (Sudharsan et al, 2020). In our study, the FCE in the birds of LOG diet was found best with highest ADG and total weight gain and lowest ADFI.…”
Section: Production Performancesupporting
confidence: 59%
“…Regarding the saturation of fatty acids, palm oil has negatively affected the productive performance of broiler chickens compared with lipids with lower saturated fatty acids concentrations like sunflower oil (Khatun et al, 2018) or rapeseed oil (Sudharsan et al, 2021). However, reductions in productive performance in broiler chickens have not always been reported when diets contain saturated or free fatty acids.…”
Section: Growth Performancementioning
confidence: 99%